Stephanofilariasis (Cascado) in Cattle - Sarwitri Endah Estuningsih (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
Stephanofilariasis which is called as Cascado is characterized by dermatitis in cattle. This disease is caused by nematode from the genus of Stephanofilaria and transmitted by the fly vector. In general, the disease is characterized by pruritis, loss of hair, ulceration, exudation and haemorrhage depending on the stage of infection. Control of the disease could be done by drug treatment of the infected animals and eradication of the fly vector periodically. The disease easily spreads, therefore farmers and the veterinary officers in the fields should pay attention on this disease.   Key words: Cascado, Stephanofilaria, cattle, fly vector, dermatitis